2017 IEEE Signal Processing in Medicine and Biology Symposium (SPMB) 2017
DOI: 10.1109/spmb.2017.8257020
|View full text |Cite
|
Sign up to set email alerts
|

Gated recurrent networks for seizure detection

Abstract: Recurrent Neural Networks (RNNs) with sophisticated units that implement a gating mechanism have emerged as powerful technique for modeling sequential signals such as speech or electroencephalography (EEG). The latter is the focus on this paper. A significant big data resource, known as the TUH EEG Corpus (TUEEG), has recently become available for EEG research, creating a unique opportunity to evaluate these recurrent units on the task of seizure detection. In this study, we compare two types of recurrent unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…By updating the data items table regularly and inviting researchers in the community to contribute, we hope to keep the supplementary material of the review relevant and up-to-date as long as possible. Provide a table or figure clearly describing your model (e.g., see [26,51,150]). 2 Clearly describe the data used.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…By updating the data items table regularly and inviting researchers in the community to contribute, we hope to keep the supplementary material of the review relevant and up-to-date as long as possible. Provide a table or figure clearly describing your model (e.g., see [26,51,150]). 2 Clearly describe the data used.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…As a result, various factors that impact the performance of DL-EEG were not covered in the review. For example, we did not cover weight initialization: in [51], the authors compared 10 different initialization methods and showed an impact on the specificity metric, with ranged from 85.1% to 96.9%. Similarly, multiple data items were collected during the review process, but were not included in the analysis.…”
Section: Limitationsmentioning
confidence: 99%
“…The depth of the convolutional network is important since the top convolutional layers tend to learn generic features while the deeper layers learn dataset specific features. The convolutional LSTM architecture with proper initialization and regularization delivers 30% sensitivity at 6 false alarms per 24 hours [10]. Feature extraction typically relies on time frequency representations of the signal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, over the past years standard RNNs and LSTMs have gone through several structural modifications which led to the rise of a simplified version of LSTM, called GRU. GRUs are widely applied and have shown their effectiveness for speech processing, medical image processing and video segmentation tasks [14,30,32]. Despite their consumption for different computer vision problems, abnormal event detection has not taken full advantage of GRUs' inherent nature to develop optimized and effective models, and much effort has not been put forth to exploit GRUs for this task.…”
Section: Introductionmentioning
confidence: 99%